Beyond Considerability: Review of Carol Freeman, Elizabeth Leane, and Yvette Watt, eds. Considering Animals: Contemporary Studies in Human-Animal Relations - Weil, Kari (Humanimalia, 2012)
Carol Freeman, Elizabeth Leane, and Yvette Watt, eds.  Considering Animals: Contemporary Studies in Human-Animal Relations. Farnham: Ashgate, 2011. xvi +236 pp. $64.95 hb.